Clinical Features and Outcomes of Tubulointerstitial Nephritis and Uveitis Syndrome in Spain and Portugal: The IBERTINU Project. (7th February 2023) - Giralt, Lena; Pérez-Fernández, Silvia; Adan, Alfredo; Figueira, Luis; Fonollosa, Alex; ,
ABSTRACT: Purpose: To assess the clinical features, management and prognosis of patients diagnosed with tubulointerstitial nephritis and uveitis (TINU) syndrome in Spain and Portugal. Methods: Retrospective multicenter study, which included all patients diagnosed with TINU syndrome managed in 15 uveitis referral centers from Spain and Portugal. Results: Forty-eight subjects with a mean age at diagnosis of 25.0 [14.8; 49.5] years were included. Both eyes were affected in 43 patients (89.6%). The visual outcome was favorable, but immunosuppressive systemic therapy (IST) was needed in 26 (54.16%) due to relapses. Renal function normalized in 35 patients (72.9%). HLA-DQB1*05 was the most common genetic typing (57.1%). The mean follow-up time was 22.5 [11.0; 48.0] months. Conclusions: Both visual and renal outcomes were favorable, although IST was frequently used. TINU is under- diagnosed, so further prospective studies would provide more knowledge about its recognition and management. Expert Opinion: TINU Syndrome is underdiagnosed because ocular and renal disease are asynchronous. Outcomes are favorable so it has to be highly suspected in cases of bilateral anterior uveitis. According to literature and our experience, systemic immunosuppressive therapy is often required because of ocular relapses. This study adds to the previous knowledge that HLA-DQB1*05 could be an important HLA type amongst the TINU Syndrome Iberian population. HLA typing should be assessed in these patients in order to describe its phenotype-genotype relationship better. A considerable number of patients in our series were diagnosed in their sixties, so TINU Syndrome should also be suspected in elderly patients.